Ultrasound-based advanced oxidation processes for landfill leachate treatment: Energy consumption, influences, mechanisms and perspectives - Yongjia Lei; Jiajie Hou; Cheng Fang; Yu Tian; Ravi Naidu; Jun Zhang; Xiaohong Zhang; Zhenxing Zeng; Zhang Cheng; Jinsong He; Dong Tian; Shihuai Deng; et al. (Ecotoxicology and Environmental Safety, 2023)
Advanced oxidation processes (AOPs) based on ultrasound (US) have attracted considerable attention in recent years due to its advantages in the degradation of landfill leachate. The review summarizes the existing treatment methods of leachate from lab-scale, compares their advantages and disadvantages by focusing on the degradation of emerging contaminants (ECs) in the leachate. Then the US-based AOPs are introduced emphatically, including their degradation mechanisms, influencing factors, energy consumption, further optimization methods as well as the possibility of field-scale application are systematically described. Moreover, this review also expounds on the advantages of dual-frequency US (DFUS) technology compared with single-frequency US, and a theoretically feasible DFUS process is proposed to treat ECs in the leachate. Finally, suggestions and prospects for US technologies in treating landfill leachate are put forward to aid future research on landfill leachate treatment. Meaningfully, this manuscript will provide reference values of US-based technologies in landfill leachate treatment for the practical use, facilitating the development of US-based AOPs in landfill leachate management and disposal.